Jane eyre - Brontë, Charlotte; Leavis, Q. D. (Penguin Books ; Viking Penguin Harmondsworth, Middlesex, England, New York, N.Y., U.S.A., 1985)
A story of passionate love, travail and final triumph. The relationship between the heroine and Mr Rochester is only one episode, albeit the most important, in a detailed fictional autobiography in which the author transmuted her own experience into high art.